Nutritional Value and In Vitro Volatile Fatty Acid Production of Forage Grasses Cultivated Using Farmyard Manure and Desmodium intortum Intercropping in the Upper Blue Nile Basin, Ethiopia - Misganaw Walie; Firew Tegegne; Yeshambel Mekuriaw; Atsushi Tsunekawa; Nobuyuki Kobayashi; Toshiyoshi Ichinohe; Nigussie Haregeweyn; Asaminew Tassew; Shigdaf Mekuriaw; Tsugiyuki Masunaga; Mitsuru Tsubo; Enyew Adgo; et al. (Advances in Agriculture)
Integrating farmyard manure (FYM) and legume intercropping improves soil chemical and microbial properties, thereby increasing forage productivity and nutritional value. The purpose of this study was to evaluate how fertilizer treatments affected the chemical composition, in vitro gas production and organic matter digestibility (IVOMD), and volatile fatty acid production (VFA) of Napier and desho grasses in the upper Blue Nile basin of Ethiopia. Apart from ether extract content, the chemical composition of the fertilizer treatments in the Aba Gerima watershed did not differ significantly, whereas significant differences were observed in acid detergent fiber and crude protein contents at the Guder watershed. In both watersheds, Napier grass had significantly higher crude protein levels than desho grass. In Aba Gerima, ash content was significantly higher in 2018 than in 2019, but not in Guder. For Napier and desho grasses, there were an increment in IVOMD (6.7 vs 4.7%), metabolizable energy (5.5 vs 4.5%), and VFA production (23.1 vs 3.0%) in the Desmodium intortum plus FYM treatment than in the control in Aba Gerima. In Guder, however, IVOMD (13.7 vs 4.6%), metabolizable energy (13.3 vs 3.3%), and VFA production (11.2 vs 5.6%) increased in the same treatment for Napier and desho grasses than in the control. This study suggests that the Desmodium intortum plus FYM improves the nutritional value, IVOMD, and VFA production of Napier and desho grasses in dryland areas of the upper Blue Nile basin, facilitating their growth as alternative livestock feed for better production in these areas.